Expression of CCR5, CXCR4 and DC-SIGN in Cervix of HIV-1 Heterosexually Infected Mexican Women - Rivera Morales, Lydia Guadalupe; López Guillén, Paulo; Vázquez Guillén, José Manuel; Palacios Saucedo, Gerardo del Carmen; Rosas Taraco, Adrián Geovanni; Ramírez Pineda, Antonio; Amaya García, Patricia Irene; Rodríguez Padilla, Cristina (2012)
Background: A number of studies have demonstrated that receptor and co-receptor expression levels which may affect viral entry, promoting cervical HIV infection. The aim was to evaluate the expression levels of CCR5, CXCR4 and DC-SIGN mRNA in a sample of heterosexually HIV infected Mexican women. Methods: We enrolled twenty-six HIV heterosexual infected women attending a local infectious diseases medical unit. RNA was isolated from the cervix and gene expression analysis was performed using real-time PCR. Results: Expression rates for mRNA of CCR5 (median 1.82; range 0.003–2934) were higher than those observed for CXCR4 (0.79; 0.0061–3312) and DC-SIGN (0.33; 0.006–532) receptors (p < 0.05). A high correlation was found between the mRNA expression levels of these three receptors (rs = 0.52 to 0.85, p < 0.01). Conclusion: Levels of expression of the tested chemokine receptors in the cervix are different from each other and also vary from woman to woman, and seem to support the suggestion that chemokine receptor expression in genital tissues may be playing a role in the HIV transmission.